ADAPTASI PENERAPAN SENGKER DEWASA UPACARA PITRA YADNYA DI DESA TAMAN BALI KABUPATEN BANGLI PADA MASA PANDEMI COVID-19 - I Ketut Sumada (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2022)
This study aims to conduct a study of the adaptation of the sengker dewasa application in Pakraman Taman Bali Village during the covid-19 pandemic. This research is designed in the type of qualitative descriptive research. This study found three results to provide answers to research problems. First, the adaptation of the application of the sengker dewasa implementation of the pitra yajña ceremony adjacent to the piodalan ceremony at the Kahyangan Tiga Temple during the covid-19 pandemic, its existence is still preserved by limiting the implementation of the pitra yajna ceremony adjacent to the piodalan. Second, the adaptation function of the sengker dewasa application in the pitra yajña ceremony adjacent to the piodalan ceremony at Kahyangan Tiga Temple during the covid-19 pandemic at least four, namely religious functions, social functions, cultural functions, and health functions. Third, the meaning of the sengker dewasa adaptation in the pitra yajña ceremony adjacent to the piodalan ceremony at Kahyangan Tiga Temple during the covid-19 pandemic at least four, namely the meaning of holiness, the meaning of health, the meaning of cultural preservation, and the meaning of solidarity. This study recommends that adaptation in the application of the sengker dewasa is very important because it contains positive potential in people's lives to always establish social relationships because the sengker dewasa is a social agreement of their ancestors which until now can still unite the Pakraman village community.